1997
DOI: 10.1007/bf02055690
|View full text |Cite
|
Sign up to set email alerts
|

Cleansing ability and tolerance of three bowel preparations for colonoscopy

Abstract: The regimen of Group C is significantly better than the regimens of Groups A or B in bowel cleansing. Regimens of Groups A and B did not differ in efficacy of cleansing. It is the timing of taking NaPh in the regimen of Group C rather than its composition that is responsible for its superior cleansing ability compared with PEG. Overnight deposition of small intestinal material in the right colon is partly responsible for the inferior cleansing ability of regimens that involve taking the solution on the day bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 6 publications
7
105
0
7
Order By: Relevance
“…Prior studies have demonstrated that split dosing not only to improves patient acceptability, but also cleans the colon better [8] . Of 13 prospective, randomized studies done previously, 12 showed superior cleansing when whole or part of the bowel preparation was given in the morning of the scheduled colonoscopy [9][10][11][12][13][14][15][16][17][18][19][20][21] . However colonoscopies are often scheduled in the afternoon, and split dosing may not leave a clean colon by afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that split dosing not only to improves patient acceptability, but also cleans the colon better [8] . Of 13 prospective, randomized studies done previously, 12 showed superior cleansing when whole or part of the bowel preparation was given in the morning of the scheduled colonoscopy [9][10][11][12][13][14][15][16][17][18][19][20][21] . However colonoscopies are often scheduled in the afternoon, and split dosing may not leave a clean colon by afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…Given the presumed antiproliferative effect of polyethylene glycol, colonic cleansing before colonoscopy was obtained using sodium phosphate, using a divided-dose regimen, the first the evening before the procedure and the second 10 to 12 hours later, as previously described (35).…”
Section: Treatment Plan and Study Proceduresmentioning
confidence: 99%
“…20 tablets are taken the night before the colonoscopy, 4 tablets every 15 minutes followed by 8 oz clear liquids and the remaining 12-20 tablets on the morning of the colonoscopy within 3-5 hours of the procedure. A split-dose NaP schedule, with one dose taken the day before and one on the day of the procedure separated by 12 hours, was also found to be superior relative to a single dose (Frommer, 1997). All NaP regimens should be taken with a minimum of 2 L of clear liquids.…”
Section: Hyperosmotic Bowel Preparationsmentioning
confidence: 99%